ENTREPRENEURIAL COMPONENT IN FORMING FINANCIAL CAPACITY OF TERRITORIAL COMMUNITIES OF KHARKIV REGION - Dymchenko, O.; Smachylo, V.; Rudachenko, O.; Shкurupiy, К. (Municipal economy of cities. Series: «Economy science», 2022)
The paper is devoted to the investigation of the theoretical and methodological foundations for the formation of the financial capacity of territorial communities (TC) in Ukraine. The object of the study are the territorial communities in the Kharkiv region, the selection criteria of which were the TC area and population size. The paper examines the budget of territorial communities, which includes revenue and expenditure parts. It has been proven that the capacity of the community shows the ability to attract, accumulate and effectively use financial resources from various sources to solve topical issues of local importance. The main advantages of the decentralization policy, which has been actively implemented in the TC of Ukraine since 2014, are given. The "Methodology for the Formation of Capable Territorial Communities" is substantiated, the results of the calculation obtained by the TC according to this methodology are given. The budget for 2021 was analyzed on the example of territorial communities of the Kharkiv region. In most territorial communities, the largest part of income is taken by tax revenues, which indicates the importance of the further mandatory development of entrepreneurial activity in communities. The results of the study showed that the analysis of the community's financial capacity showed that, indeed, budget decentralization measures had a rather positive effect on the financial capacity of TС budgets. However, the independence of local self-government bodies, which is one of the main ideas of budget decentralization, is determined not only by the amount of financial resources, but also by the reason for their increase. However, territorial communities should remember that transfers and other financial assistance from central authorities are temporary funds: today the state allocates them, but tomorrow it does not. Therefore, the TС should rely on its own capabilities in the accumulation of tax and non-tax revenues, thereby emphasizing the development of entrepreneurship from small to large.